The Reality of Indonesian Marriage Law Concerning Post-Divorce Child Custody - Putra, M. Taufan Perdana; Alfaris, M. (Politeknik Harapan Bangsa Surakarta, 2021)
This paper re-constructs how the reality of Indonesian marriage law is related to the decision on child rights disputes after divorce. Ideally, marriage wants the couple to be a happy and lasting family bond without ending in divorce. Legal events such as divorce, instead of being a solution to family problems, will actually cause new problems such as property or child disputes. The purpose of this study is to reveal how the reality of marriage law works, especially with regard to court decisions regarding child custody disputes. descriptive-analytical research method, an in-depth academic search related to this issue is certainly still a must, given the importance of this study as a means and recommendation to related parties in anticipating and reducing the reality of the high divorce rate in Indonesia. The panel of judges can break away from normative regulatory ties as long as it will bring justice and benefit to children. Child custody, for certain reasons such as the principle of appropriateness and propriety, even though juridically if before the child is 12 years old, custody of the child is in the power of the mother, it can fall to the father as long as the panel judges with sufficient evidence and testimony. However, this attitude still has a claim of legality from both theoretical sources and statutory regulations, and even becomes a reflection of the accommodation of the family relationship pattern entity that still upholds local cultural values.